2014
DOI: 10.1089/tmj.2013.0037
|View full text |Cite
|
Sign up to set email alerts
|

Shared Care Combined with Telecare Improves Glycemic Control of Diabetic Patients in a Rural Underserved Community

Abstract: Shared care combined with telecare could significantly reduce HbA1c levels in type 2 diabetic patients with poor glycemic control in underserved rural communities. Further studies should be conducted to clarify the target users and to develop cost-effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
0
26
0
2
Order By: Relevance
“…A study conducted in a rural setting [ 53 ], showed an improvement in HbA1c levels among patients exposed to diabetes education with interactive online sessions, delivered by a multidisciplinary team (0.7 ± 1.3% vs 0.1 ± 1.0%; p < 0.03 after adjustment for baseline HbA1c, n = 95).…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in a rural setting [ 53 ], showed an improvement in HbA1c levels among patients exposed to diabetes education with interactive online sessions, delivered by a multidisciplinary team (0.7 ± 1.3% vs 0.1 ± 1.0%; p < 0.03 after adjustment for baseline HbA1c, n = 95).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 32 interventions, 18 (56%) were PDA-, tablet-, computer-, or mobile phone–delivered or Web-based interventions [ 6 , 25 , 31 , 33 , 58 , 60 , 61 , 68 - 71 , 74 - 80 ], 7 interventions (22%) were telehealth interventions delivered via landline telephones [ 57 , 59 , 63 , 66 , 67 , 73 , 81 ], 6 (19%) used text messaging [ 20 , 56 , 62 , 64 , 65 , 72 ], and 1 employed videoconferencing [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Jedoch wurde durch die Internationalität des Scoping Reviews der Selektionsbias minimiert. Delegative Leistungen werden bisher oft in Modellvorhaben in unterversorgten Gebieten durchgeführt und zeigen teilweise ähnliche Resultate [36][37][38]. Ein flächendeckendes Versorgungsmodell könnte daher einen innovativen Lösungsbeitrag zur Behebung des Ärztemangels darstellen.…”
Section: Diskussion Und Schlussfolgerungenunclassified
“…Ein flächendeckendes Versorgungsmodell könnte daher einen innovativen Lösungsbeitrag zur Behebung des Ärztemangels darstellen. Ebenso bietet die vorliegende ökonomische Analyse eine Grundlage für die Diskussion um eine leistungsgerechte Vergütung delegativer Leistungen, wie sie von Hausärzten gefordert werden [35][36][37][38][39]. Eine Steigerung der innerbetrieblichen Effektivität und Effizienz durch eine verbesserte Praxisorganisation konnte in den vorliegenden Studien teilweise nachgewiesen werden [27][28][29][30][31][32], wurde jedoch häufig durch hohe Implementierungskosten verdeckt.…”
Section: Diskussion Und Schlussfolgerungenunclassified